An evaluation of the performance diagnostic checklist : human service to guide intervention selection to increase treatment integrity of preschool teachers - Anna Marín Skúladóttir 1987- (2022)
Applied Behavior Analysis (ABA) applies the science of human behavior to improve behavior of social significance (Baer et al., 1968). ABA therapy is considered the gold standard in treating children with developmental disabilities (Newcomb & Hagopian, 2018). However, its effectiveness is only as good as the treatment implemented (Fryling et al., 2012). Treatment integrity refers to how the independent variable is implemented with precision (Peterson et al., 1982). High treatment integrity is essential for clients' improvements and progress (McIntyre et al., 2007). A Board Certified Behavior Analyst (BCBA) typically develops an idiosyncratic program for the client to meet their needs and the Registered Behavior Technician (RBT) implements the designed program. In Iceland, we do not have RBTs, so the preschool teachers often need to implement the treatments. There is a need to understand the barriers for teachers to implement the treatment with integrity. The purpose of this study was to evaluate if the Performance Diagnostic Checklist-Human Service could guide intervention selection to increase teachers' implementation of Discrete Trial Training (DTT), token-system, and MSWO in a preschool in Iceland. We recruited three special education teachers from two Icelandic preschools that had finished the course Skráning og Þjálfun held by the State Counselling and Diagnostic Center. The dependent variable was the teacher's treatment integrity in implementing DTT, token system, and MSWO. The results showed that the PDC-HS was successful in guiding intervention selection, task clarification and training, to increase teachers' implementation of Discrete Trial Training, token-system, and MSWO. Keywords: Performance Diagnostic Checklist – Human Service, Treatment Integrity, Behavioral Skills Training, Special Education